RANCANG BANGUN OVEN KUE DENGAN DUA SUMBER PANAS - Muhammad Naim; Aziz Asmauna; Ika Surika; Muh. Taufiq Mangkali (Dinamika : Jurnal Ilmiah Teknik Mesin, 2019)
Designing a cake oven with two heat sources is a study that aims to design and make cake ovens that can produce an oven that has heat spread evenly on each gutter, and the time and temperature of the oven can be adjusted according to needs. This study discusses about ovens made operated with a choice of 2 types of heat sources namely electricity and gas, gas as an alternative source of heat, maximum heating temperature of 120oC, research using library research methods and field research methods namely interviews and direct observation of oven use cake. Based on the research carried out the results of oven cake with 2 heat sources were obtained from the electrical element and from the gas stove. Based on the results of oven cake tests using electric heating elements obtained the temperature on chamfer one 112 °C, chamfer two 110 °C and chamfer three 105 °C. The test results using gas obtained temperature on gutters one 125 °C, gutters two 115 °C, and gutters three 120 °C. In the oven cake thermostats are added as readers of the temperature in the oven, thermocouple as a temperature sensor, timer as a roasting timer in the oven, and SSR (Solid State Rellay) as an automatic switch.